High magnetostriction coefficient of Mn substituted cobalt ferrite sintered from nanocrystalline powders and after magnetic field annealing - Mohaideen, Kamal Khaja; Joy, Pattayil Alias (Current Applied Physics, 2013)
Magnetostriction characteristics of Mn substituted cobalt ferrite, CoFe2-xMnxO4 (0 <= x <= 0.3), sintered from nanocrystalline powders of average particle size of similar to 4 nm have been studied. Larger value of magnetostriction at lower magnetic field is achieved after substitution of Mn for Fe. The maximum value of magnetostriction coefficient is not much affected and the slope of the magnetostriction is increased with increasing Mn content. Higher maximum value of magnetostriction coefficient (lambda) of 234 ppm comparable to that of the unsubstituted composition with larger strain derivative (d lambda/dH) is obtained for x = 0.2 in CoFe2-xMnxO4. The magnetostriction coefficient is increased to 262 ppm with further enhancement in the strain derivative after annealing the sintered compact at 300 degrees C in a magnetic field of 400 kA/m for 30 min. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Cobalt ferrite; Magnetic field annealing; Magnetostriction; Mn substitution; Nanocrystalline